Responsibility Effects in Decision Making under Risk - Julius Pahlke; Sebastian Strasser; Ferdinand M. Vieider (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
We systematically explore decision situations in which a decision maker bears responsibility for somebody else's outcomes as well as for her own in situations of payoff equality. In the gain domain we confirm the intuition that being responsible for somebody else's payoffs increases risk aversion. This is however not attributable to a 'cautious shift' as often thought. Indeed, looking at risk attitudes in the loss domain, we find an increase in risk seeking under responsibility. This raises issues about the nature of various decision biases under risk, and to what extent changed behavior under responsibility may depend on a social norm of caution in situations of responsibility versus naive corrections from perceived biases. To further explore this issue, we designed a second experiment to explore risk-taking behavior for gain prospects offering very small or very large probabilities of winning. For large probabilities, we find increased risk aversion, thus confirming our earlier finding. For small probabilities however, we find an increase of risk seeking under conditions of responsibility. The latter finding thus discredits hypotheses of a social rule dictating caution under responsibility, and can be explained through flexible self-correction models predicting an accentuation of the fourfold pattern of risk attitudes predicted by prospect theory. An additional accountability mechanism does not change risk behavior, except for mixed prospects, in which it reduces loss aversion. This indicates that loss aversion is of a fundamentally different nature than probability weighting or utility curvature. Implications for debiasing are discussed.
urn:nbn:de:bvb:19-epub-12115-3
Keywords: D03; D81; 330; risk attitude; other-regarding preferences; prospect theory; agency; social norms; Entscheidung bei Risiko; Risikopräferenz; Verantwortung; Soziale Beziehungen; Soziale Norm; Prospect Theory; Test